Permanent education applied to professionals in the hemotherapy sector: an integrating review (Research, Society and Development, 2021)
Blood transfusion is still the only method of choice for some pathologies. Currently, even with all investment, blood transfusion can still bring risks to the patient. The aim of the study was to demonstrate whether continuing education in health is being applied in the hemotherapy sector, both nationally and internationally. It is an integrating review, of a descriptive and exploratory nature, through the search in the PubMed, BVS and CAPES databases. 207 articles were found and 3 selected, after applying the exclusion criteria for the complete reading and synthesis. Two were in English and one was in Portuguese. The years of publication were 2013, 2016 and 2019. As for the professionals surveyed, 2 articles addressed nurses and 1 addressed a multidisciplinary team. All articles were intended to increase transfusion safety, but did not include all professionals involved in the sector. Professionals report the need for educational policies, but express a preference for policies that involve everyday situations and are active. Although permanent health education involves significant learning and its benefits are already known, the literature does not address the topic directly and there were few articles related to this type of learning. It became apparent that training programs related to transfusion must undergo changes. Learning where there is team involvement and everyday situations increases learning, increasing the quality of service. Educational improvement must be a continuous and permanent process.